Percieved Threat of Homosexuals in Indonesia: Construct, Measurement, and Correlates - Tjipto, Susana; Mayawati, Elisabeth Haksi; Bernardo, Allan B. I. (Makara Human Behavior Studies in Asia, 2019)
In Indonesia, homonegativity still exists and acts of violence against homosexual groups still happen, but there has not been much research on aspects of this homonegativity beyond inquiring into general attitudes towards homosexuals. This study has several aims: to qualitatively explore dimensions of perceived threat, to develop a measure of perceived threat of homosexuals, and to study some correlates and perceived threat of homosexuals in Indonesian samples. We used a mixed-method approach (qualitative-quantitative) to gather the data. Study 1 is a qualitative study that seeks to identify expressions and dimensions of perceived threat of homosexuals using thematic analysis of responses to an open-ended questionnaire and of online media articles. Study 2 develops a measure of perceived threat of homosexuals based on the results of Study 1, then establishes the factor structure and reliability of the measure, and explores some correlates of the measure. developed. The implications of using the scale to further study homonegativity in Indonesia and other Asian societies is discussed